1997
DOI: 10.1523/jneurosci.17-10-03870.1997
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of the Caudate Nucleus in Primates Performing Spatial and Nonspatial Working Memory Tasks

Abstract: The caudate nucleus is part of an anatomical network subserving functions associated with the dorsolateral prefrontal cortex (DLPFC). The aim of the present study was to investigate whether the metabolic activity in the striatum reflects specific changes in working memory tasks, which are known to be dependent on the DLPFC, and whether these changes reflect the topographic ordering of prefrontal connections within the striatum. Local cerebral glucose utilization (LCGU) rates were assessed in the striatum by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
133
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(147 citation statements)
references
References 65 publications
(92 reference statements)
9
133
1
4
Order By: Relevance
“…During the delay periods of delayed-response tasks, striatal neurons exhibit sustained activity that closely resembles that of the DLPFC (Apicella et al, 1992). Such findings have led to the hypothesis that this circuitry plays a role in maintaining tonic activity of the DLPFC during maintenance periods in which information critical to a correct response is held "on line" (Goldman-Rakic, 1995;Levy et al, 1997). Positive feedback in these reverberating loops has been hypothesized to provide a mechanism for sustaining WM (Beiser and Houk, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…During the delay periods of delayed-response tasks, striatal neurons exhibit sustained activity that closely resembles that of the DLPFC (Apicella et al, 1992). Such findings have led to the hypothesis that this circuitry plays a role in maintaining tonic activity of the DLPFC during maintenance periods in which information critical to a correct response is held "on line" (Goldman-Rakic, 1995;Levy et al, 1997). Positive feedback in these reverberating loops has been hypothesized to provide a mechanism for sustaining WM (Beiser and Houk, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia play important roles in the regulation of both motor and non-motor functions (9)(10)(11), and motor abnormalities can occur in neuroleptic-naïve schizophrenia patients (12). Basal ganglia dysfunction, assessed with functional MRI, has been reported in schizophrenia and their unaffected siblings (13)(14)(15).…”
mentioning
confidence: 99%
“…In this regard, it was suggested that the effects of neuroleptics in the caudate may be subordinate to those upon the putamen in terms of elevating functional activity (Prince et al 1998a). This is of importance based upon recent evidence that the caudate is involved in working memory (Levy et al 1997). Thus, an alternative explanation in this matter is that a lack of correlation in the caudate in schizophrenics may itself be "pathological" and suggestive of damaged circuitry.…”
Section: Discussionmentioning
confidence: 99%